Identification of Cookies Quality Based on Banana Flour (Musa acuminata Colla) and “Selengek” Fish Flour (Anodontostoma chacunda) - Hesti Nur'aini; Febrian Sutata; Lina Widawati (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Negeri Tanah Laut, 2025)
“Jantan” banana (Musa acuminata Colla) and “selengek” fish (Anodontostoma chacunda) have high nutritional value, so they have the potential to be used as additional ingredients in cookie processing. This study aimed to analyse the quality characteristics of banana flour and selengek fish flour-based cookies. The research design used was factorial with variations in the composition of male banana flour and “selengek” fish flour, namely 75: 25, 80 : 20, 85 : 15, 90 : 10, 95 : 5, and 100 : 0. Chemical analysis (moisture content, protein content, and fibre content) and organoleptic test (colour, taste, aroma, and texture) were conducted on the cookies produced. Processing of cookies with the addition of male banana flour and selengek fish flour produced cookies with yields between 40.58% to 41.20%, moisture content between 6.11% to 8.58%, protein content 4.23% to 5.69%, and fibre content 5.00% to 6.19%. Sensory test analysis showed that panelists' hedonic level for banana flour and “selengek” fishmeal cookies ranged from 3.35 to 2.40 for colour parameters, 2.40 to 3.70 for taste parameters, 2.90 to 4.04 for texture and 2.40 to 3.35 for aroma parameters.